LANGUAGE, IDEOLOGY AND POWER RELATION REFLECTED IN THE EDITORIALS NEWS OF THE JAKARTA POST AND THE JAKARTA GLOBE - Winarsih, Sri (2010)
The object of the research is the editorial news of The Jakarta Post and The Jakarta globe. The major problem of this study is how the language, ideology and power relation is reflected in editorials news The Jakarta Post and The Jakarta Globe. Therefore, the study analyzes the editorials news based on structural element of the newspaper and analyzes social cognition and historical context. The type of this study is qualitative study. The writer uses two data sources: they are primary data sources and secondary data sources. The primary data sources and the object of the study is the editorial news itself. Meanwhile the secondary data sources are the other source which relates to the primary data sources such as journal, and website about the newspaper. Themethod of the data collection is library research by collecting both primary and secondary data.The technique of data analysis is descriptive analysis based on critical discourse analysis. The result of the analysis shows the following conclusions: First language of The JakartaPost and The Jakarta Globe is interrelated with ideology. Second, ideology of The Jakarta Post and The Jakarta Globe is interested serve that political interest is subject to economic interest. Third, the power relation between both newspapers is different, the dominant power of The Jakarta Post is political power and The Jakarta Globe is economic power.